Quantification of Thiamine in Edible Bird’s Nest by HPLC with Fluorescence Detection - Teo, Peishan; Ma, Fucui; Liu, Daicheng (Asian Journal of Chemistry, 2014)
Edible bird's nest is the nest made from saliva of swiftlets. In the Tang (618-907 AD) and Song (960-1279 AD) dynasties, edible bird's nest is a traditional Chinese medicine. As time changes, it becomes a perfect nutraceutical food for the easterners in daily diet. People attach importance to the edible bird's nest for the study of bioactive constituents. The study of vitamin was rarely conducted in the edible bird's nest, especially B-complex. We detected thiamine in the edible bird's nest for the first time. The method used a C18 analytical column 150 mm × 4.6 mm, 5 μm (Hypersil-ODS2). The aqueous mobile phase contained methyl alcohol and sodium acetate solution (34: 66) (v/v). Separation and quantification was achieved by changing the proportion of the system linearly with a time-schedule programme. Detection was carried out using fluorescence detection set at 365 nm excitation wavelength and 475 nm emission wavelength.